2022
DOI: 10.1007/s40520-022-02258-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and associated factors for swallowing impairment in community-dwelling older persons: a systematic review and meta-analysis

Abstract: Introduction Swallowing impairment (SI) is an underdiagnosed dysfunction frequently seen as an expected condition of aging. However, SI can lead to health complications and considerable social impact. Methods The objective of this systematic review with meta-analysis was to evaluate the frequency and associated factors with SI in community-dwelling older persons. Searches were performed in 13 electronic databases including MEDLINE and EMBASE (from inception to September 18, 2021). Data extraction and methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Oral diadochokinesis examinations are considered inappropriate for older people under these conditions. It is appropriate as an oral function test for community‐dwelling people with maintained physical and cognitive functions 11,19–23 . However, OD test as a method to evaluate the oral function of nursing home residents with reduced physical and cognitive functions is considered unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Oral diadochokinesis examinations are considered inappropriate for older people under these conditions. It is appropriate as an oral function test for community‐dwelling people with maintained physical and cognitive functions 11,19–23 . However, OD test as a method to evaluate the oral function of nursing home residents with reduced physical and cognitive functions is considered unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in pronouncing the same syllable consecutively, even when assessing only the clarity of pronunciation, underlies this result. ODK is a measure of lip and tongue motor functions but is also associated with dysphagia [31] and tongue coating [32]. Therefore, if it is difficult to assess persons with severe dementia, other assessment methods should be considered depending on the purpose of assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relation between swallowing function and aging, a recent systemic review and metaanalysis indicated that the main factors associated with age-related dysphagia were dry mouth and oral sensorimotor alteration [20]. Another review suggested that esophageal sensation decays with age, and several neuromuscular and structural disorders may cause oropharyngeal dysphagia [18], which in turn causes vallecular residues and poor oral intake at discharge [18].…”
Section: Association Between Age and Oral Intake At Dischargementioning
confidence: 99%